Legal expertise of the legal acts as law category and scientific doctrine - Рибікова, Ганна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article is devoted to researching the modern scientific views on the problem of the legal acts’ examination.In this investigation the author determines the basic approaches of understanding the place and valueof legal expertise of the legal acts.